2019
DOI: 10.1007/s40119-019-0132-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Outcome Measures for Coronary Artery Disease Value-Based Contracting Using the Delphi Method

Abstract: Introduction Value-based contracts (VBCs) that link drug payments to disease-related performance metrics aim to increase the value and lower the cost of medications by aligning incentives and sharing risk between payers and pharmaceutical manufacturers. This study sought to identify outcome measures that are meaningful to key stakeholders to inform VBCs for coronary artery disease (CAD) medications. Methods We administered a modified Delphi survey to gather expert opini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In our review, it was found that administrative data were the least frequently used source for outcome measurement, and they were limited to measures such as survival and mortality [ 40 , 41 , 43 , 45 , 50 , 52 , 56 61 , 64 66 , 69 – 72 , 75 , 76 ]. Data reported by clinicians and patients were more frequently used in the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review, it was found that administrative data were the least frequently used source for outcome measurement, and they were limited to measures such as survival and mortality [ 40 , 41 , 43 , 45 , 50 , 52 , 56 61 , 64 66 , 69 – 72 , 75 , 76 ]. Data reported by clinicians and patients were more frequently used in the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, patients were involved in the development of the standardized outcome sets to ensure that their perspectives were incorporated into measures development [ 39 , 42 , 45 , 55 58 , 60 , 64 , 68 71 , 74 , 75 ]. Relevant PROMs can orient the patients about the potential outcomes of their medical condition and, at the same time, solicit feedback on their needs and priorities regarding the delivered treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…This may be measured according to several characteristics including income, employment, education, disability, crime, housing and services and living environment deprivation. Because there is no universal recommendation for core outcome sets in studies on CVD prevention,19–21 studies will be eligible for inclusion regardless of outcomes measured or reported for health outcomes, this may include vascular-related outcomes, cognitive and functional outcomes, lifestyle, medical risk factors, cardioprotective medications and patient-reported outcome measures. Any measures of professionals’, patients’ and/or families’ knowledge, attitudes or satisfaction will also be included.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In Round 2, the panel's collective Round 1 rating of each outcome was displayed alongside the individual's original Round 1 rating, following Delphi study methodology. [23][24][25]40,41,42 For example, if in Round 1 a participant rated a given outcome as "slightly important" (2) and the average panel rating for that outcome was "3.50," both descriptors were displayed alongside each outcome in the Round 2 survey. Stakeholders were given the opportunity to adjust their Round 2 outcome ratings based on the collective panel information.…”
Section: Methodsmentioning
confidence: 99%
“…Stakeholders who completed the Round 1 survey were eligible to complete the Round 2 survey. In Round 2, the panel’s collective Round 1 rating of each outcome was displayed alongside the individual’s original Round 1 rating, following Delphi study methodology 23‐25,40,41,42 . For example, if in Round 1 a participant rated a given outcome as “slightly important” (2) and the average panel rating for that outcome was “3.50,” both descriptors were displayed alongside each outcome in the Round 2 survey.…”
Section: Methodsmentioning
confidence: 99%